EVOLUTION OF LITERARY CRITICISM: A HISTORICAL PERSPECTIVE (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract:This article explores the historical evolution of literary criticism, tracing its roots from classical antiquity to contemporary theories. Starting with Aristotle's Poetics, it highlights key developments through the Renaissance's neoclassicism, the Romantic emphasis on individual expression, and the emergence of New Criticism in the 20th century. The article examines how various movements, such as structuralism and postmodernism, have shaped modern literary theory, influencing interpretations of texts and authorship. Ultimately, it underscores the dynamic interplay between literature and criticism across different historical contexts, reflecting broader cultural and philosophical shifts.